The effectiveness of activity based interventions in the management of overweight and obesity in children – a systematic review - Ezenwugo, Chibuzo Ngozi (My University, 2020)
BACKGROUND: Childhood overweight and obesity is a disease that constitutes a current global pandemic. It leads to a series of morbid medical conditions which progress into adulthood. Sedentary living, unhealthy diets and the over-reliance on technology are implicated as reasons for the current pandemic. Concurrent aerobic and resistance exercises are an effective combination of physical activity interventions relevant for altering the body’s energy expenditure. Physical activity interventions should be administered in conjunction with dietary control to ensure success. Furthermore, literature suggests that behavioural interventions, family involvement and prolonged monitoring will increase the likelihood of sustained weight loss. AIM: To determine whether physical activity based interventions are effective in the management of overweight and obesity in children METHODS: A comprehensive internet search identified randomised controlled trials published between January 2002 and February 2018 that used the BMI z-score to assess the efficacy of sole physical activity interventions in dealing with overweight/obesity in children aged 6-12-year-old. RESULTS: Four studies were included in this systematic review. The risk of bias for each study was low. Physical activity interventions all resulted in a reduction of the BMI z-score, however, the degree of BMI z-score reduction varied between studies. The review results also showed that during the follow-up period, when direct supervision was removed, many participants regained some of the weight lost. CONCLUSION: Sole physical activity based interventions are effective in reducing BMI z-score of overweight and obese children. Activity interventions should be conducted thrice weekly for about an hour and should include both aerobic and resistance exercises. However, multimodal interventions inclusive of diet, exercise and behaviour modification supersedes sole activity interventions in efficacy. A family supported dietary intervention with behavioural modification should be the first line of action followed subsequently by a long-term activity lifestyle change. Sustained weight loss often poses a challenge in most overweight and obesity management programmes. Family involvement and prolonged monitoring increase the likelihood of sustaining weight loss
A dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the Master of Science in Physiotherapy, 2020